Developing Mind Mapping-Based Teaching Materials for Teaching Self-Care Skill Adaptive Behavior to Students with Multiple Disabilities Visual Impairment (MDVI) - Susanti, Dewi Juwita; Rudiyati, Sari (Journal of ICSAR, 2023)
Limitations on more than one aspect, cause multiple disability visual impairment (MDVI) students to experience obstacles in carrying out daily activities related to self-care skills. Students need adaptive behavioral learning to provide them with self-reliance. However, teaching materials for adaptive behavior learning are limited. Teachers need teaching materials that can accommodate the learning process of adaptive behavior for students with MDVI. This study aims to develop mind-mapping-based teaching materials for adaptive behavior. Research and development refer to the steps of the ADDIE model. The results of the study explain that the teaching materials are feasible based on assessments from material experts, media experts, and practitioners so that they can be used in the learning process. The teaching materials developed can be the solution for teachers in the process of teaching adaptive behavior for students with MDVI to be skilled in carrying out daily activities.